Literature Review on the Development Trends of Gene-Modified Cell Therapies: Focusing on clinical studies of TCR-T cell therapy - Kim, Jongyoon; Lee, Hyang-Mi (Korean Journal of Clinical Pharmacy, 2025)
Immunotherapy has transformed cancer treatment in the past decade, with combinations of immune checkpoint inhibitors and conventional therapies showing promise across various cancers. This study reviews ongoing clinical trials of T cell receptor-T cell (TCR-T) therapies, analyzing their potential in targeting key cancer antigens for future treatment advancements. We examined data from ClinicalTrials.gov, focusing on phase 1-4 trials with reported results up to August 31, 2024. Trials were selected based on relevance to TCR-T cell therapy, safety and efficacy evaluation, and predefined inclusion/exclusion criteria. Thirty-three TCR-T clinical trials were identified, with 17 focusing on advanced cancers. Target antigens included New York esophageal squamous cell carcinoma (16 trials), melanoma-associated antigen (5 trials), and human papillomavirus 16 E (4 trials). Most studies targeted adults, with three involving pediatric patients. Sponsors included the National Cancer Institute and GlaxoSmithKline, with melanoma being the most studied cancer. One trial (NCT05066165) utilized CRISPR/Cas9 for non-viral TCR gene editing. Recent FDA approval of afamitresgene autoleucel, the first gene-modified TCR-T cell therapy targeting solid tumors, marks a significant milestone. TCR-T therapies are evolving into personalized cancer treatments, with shared antigenbased therapies leading development. The introduction of CRISPR technology is expected to enhance the efficiency and safety of gene-modified therapies, shaping the future of cancer immunotherapy. This review highlights the rapidly advancing field of TCR-T cell therapies and their potential to revolutionize cancer treatment. KCI Citation Count: 0